2022
DOI: 10.1002/advs.202204502
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Biomaterials for Facilitating Bone Defect Repair under Pathological Conditions

Abstract: Bone degeneration associated with various diseases is increasing due to rapid aging, sedentary lifestyles, and unhealthy diets. Living bone tissue has bioelectric properties critical to bone remodeling, and bone degeneration under various pathological conditions results in significant changes to these bioelectric properties. There is growing interest in utilizing biomimetic electroactive biomaterials that recapitulate the natural electrophysiological microenvironment of healthy bone tissue to promote bone repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 234 publications
(505 reference statements)
0
15
0
Order By: Relevance
“…70,71,77−81 The modulation of macrophage behavior is typically dependent on the material surface properties such as surface potential, surface roughness, and hydrophobicity. 70,81 Particularly for piezoelectric materials, the dynamic surface potential generated at the cell−material interface is known to influence the cell behavior significantly. 79,80 For instance, Zhou et al in 2023 studied the influence of differing surface potential generation from piezoelectric PVDF−TrFE films on macrophage polarization for accelerated wound recovery.…”
Section: Electrical Stimulation Viamentioning
confidence: 99%
See 1 more Smart Citation
“…70,71,77−81 The modulation of macrophage behavior is typically dependent on the material surface properties such as surface potential, surface roughness, and hydrophobicity. 70,81 Particularly for piezoelectric materials, the dynamic surface potential generated at the cell−material interface is known to influence the cell behavior significantly. 79,80 For instance, Zhou et al in 2023 studied the influence of differing surface potential generation from piezoelectric PVDF−TrFE films on macrophage polarization for accelerated wound recovery.…”
Section: Electrical Stimulation Viamentioning
confidence: 99%
“…Due to their high biocompatibility and biodegradability, piezoelectric polymers such as PVDF–TrFE and poly­(hydroxybutyrate- co -valerate) (PHBV) have shown promising results in transitioning the phenotypes of macrophages for the systematic repair of wounds in a self-powered manner. ,, The modulation of macrophage behavior is typically dependent on the material surface properties such as surface potential, surface roughness, and hydrophobicity. , Particularly for piezoelectric materials, the dynamic surface potential generated at the cell–material interface is known to influence the cell behavior significantly. , For instance, Zhou et al in 2023 studied the influence of differing surface potential generation from piezoelectric PVDF–TrFE films on macrophage polarization for accelerated wound recovery . The as-prepared PVDF–TrFE films were first polarized with electric field intensities of 50 V/μm (low polarized) and 100 V/μm (high polarized), which generated surface potentials of 19 ± 13 and 232 ± 7 mV, respectively, and macrophages were seeded on their surfaces.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
“…Among them, electrical stimulation is an attractive option because it has been demonstrated that sending signals across cell membranes with −10 to −90 mV would encourage cells to travel to the site of injury, 10 and also boost cardiac, 11 nerve, 12,13 and bone tissue regeneration. 14,15 Therefore, electroactive scaffolds have emerged as a promising solution for bone therapies because they could deliver electrical stimulation directly to cells to improve incorporation, growth, and formation of new bone tissue. 9,16…”
Section: Introductionmentioning
confidence: 99%
“…Among them, electrical stimulation is an attractive option because it has been demonstrated that sending signals across cell membranes with À10 to À90 mV would encourage cells to travel to the site of injury, 10 and also boost cardiac, 11 nerve, 12,13 and bone tissue regeneration. 14,15 Therefore, electroactive scaffolds have emerged as a promising solution for bone therapies because they could deliver electrical stimulation directly to cells to improve incorporation, growth, and formation of new bone tissue. 9,16 Electroactive scaffolds can be prepared by combining nonconductive biocompatible and biodegradable polymers, such as polycaprolactone (PCL), with conductive fillers, such as carbonbased, 17,18 conductive polymeric-based, 9,19 or metallic-based nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are an emerging class of crystalline porous material with structural regularity, simple accessibility, chemical stability, and built-in functional tunability at the molecular level. To date, many COFs have been synthesized and have shown great potential for applications in various fields such as gas separation and storage, optoelectronics, energy storage, and catalysis. Among all COFs, owing to the photosensitive 18π aromatic macrocyclic nature of MPc, constructing COFs with MPc units provides an opportunity for the development of electrochemical materials and has recently become a hot research topic. In 2021, two novel pyrazine (pz)-linked metal-phthalocyanine (MPc)-based conjugated 2D COFs were constructed by the Feng group . Most relevantly, Jiang et al reported that phenazine-linked Co-phthalocyanine COFs (CoPc-PDQ-COFs) with high stability and conductivity were used as efficient electrocatalysts for the CO 2 RR .…”
mentioning
confidence: 99%